ANALISIS PENGEMBANGAN ELECTRONIC GOVERNMENT MELALUI PENYELENGGARAAN WEBSITE DI KABUPATEN KUDUS - Muhammad Syaiful Arif; Endang Larasati; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2013)
Use of information technology is very important in government institutions, such as the electronic government, where the government attempted to improve service to the community in a more convenient, fast, effective and efficient. Development of e-government in Kudus district that has not run up pushing me to do this research. The research problem is : How does the development of e-government in Kudus district? and what constraints the development of e-government in Kudus district?.The purpose of this study to describe and analyze how the development of e-government and to describe the obstacles faced by the development of e-government in the District of Kudus. To answer the problem and the research objectives using successful elements of e-government development in the Harvard JFK School of Government, namely : support, capacity, and value. It also uses elements of the development of e-government according to Moon in Book Information Management System consists of a willingness and local culture. This study uses descriptive qualitative sample snowballing technique so that it can be explained the extent to which the development of e-government in the District of Kudus. There are two sources of data were used, namely primary and secondary data. This study using in-depth interviews, observation, and documentation as well as triangulation associated with the development of electronic government in Kudus district in collecting the data.The results showed that the implementation of e-government in the District of Kudus has not been able to run optimally because there are issues that affect development, as there is no support in the implementation of e-government in the absence of the political will of the government's full and socialization. Capacity is very limited financial resources, human resources and technology infrastructure is still inadequate . The absence of public willingness to use and avail the facility of e-government as well as the cultural/local culture Kudus Regency society who prefer the manual way instead of using information technologies in a variety of jobs.